PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DENGAN MEMANFAATKAN MEDIA GAMBAR TERHADAP HASIL BELAJAR BIOLOGI - ' Azrul, Ulfia Rahmi (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The purpose this is to increase students learning outcomes biology class by using cooperative learning model think pair share type using picture media. This research is class action research (CAR). Subject of this research is students in junior high school whit totals 20 students consist of 9 male students and 11 female students. The collecting data of this research using descriptive analysis. The data that analyzed are result of science understanding concept and scientific performance. The student’s capacity of learning outcome before CAR is 69,25 and increase amount of 13,24% first cycle become 82,49 and on the second cycle increase amount of 5,21% become 87,70. Can be summery that application of cooperative learning think pair share type using picture media can increase the result of students learning biology class.Key Words: Cooperative Learning Model, Think Pair Share